Index Morphotectonic Of Morphology In The Patukuki Watershed Region, Peling Tengah District, Banggai Kepulauan - Sukardan Tawil; Bayu Saputra; Abdul Mukaddas; Asrafil (LPPM Universitas Tadulako, 2021)
Introduction: The Patukuki area in the Central Peling sub-district falls administratively within the geographical coordinates of 123°01'00